Sufentanil in combination with low-dose hyperbaric bupivacaine in spinal anesthesia for cesarean section: a randomized clinical trial - Dourado,Alexandre Dubeux (2016)
Abstract A double blind randomized clinical trial of sufentanil as an adjunct in spinal anesthesia for cesarean section and, thereby, be able to reduce the dose of bupivacaine, a local anesthetic, with the same result of an anesthetic block with higher doses but with fewer perioperative side effects, such as hypotension.